PENINGKATAN KOMPETENSI BERBICARA GURU BAHASA JERMAN DENGAN MENGGUNAKAN MEDIA DIGITAL - Wilma Akihary; Rita Fransina Maruanaya; Carolina Lestuny; Selina Irnleitner (German für Gesellschaft (J-Gefüge), 2022)
The activity under the title Improving the Speaking Competence of German Language Teachers using Digital Media aims to improve German speaking skills of teachers at the BI level by using digital media. The importance of improving teachers' speaking skills, is one of the factors supporting the career of German language teachers, in addition to their pedagogical competence. Beside of that, teachers can apply it in the process of learning German in class. The expectation is teachers are able to develop themselves and learn for the advancement of their career and compete globally. According to observations, it is seen that not all teachers understand the model test of German language skills at level B1. In addition, some teachers still do not take advantage of developing digital media to improve language competence. One of the language skills that is deemed necessary to be trained is speaking. As one of the productive competencies, speaking skills need to be trained continuously as part of improving language competence. As an institution which produces professional educators, Faculty of Teacher Training and Education Pattimura University needs to provide knowledge and experience in helping German language teachers improve speaking competence at B1 level. This activity involved 16 German Language teachers from high school in West Seram Regency. The used methods were varied, namely playing, lecturing, question and answer, discussion, partner work and group work. This activity is carried out in several stages. First, it begins with the introduction of the B1 level of speaking competency test. Second, providing material about digital media and techniques that can be used. Third, implementation. In this stage, the teachers practiced speaking with partners. Then they discussed and working the task in groups. Finally, presenting the project of the group's work about tourism spot in West Seram